Stress, Trauma, Sepsis, Inflammation, Management in Asthma - Marianne Frieri; Krishan Kumar; Anthony Boutin (Open Journal of Asthma - Peertechz Publications, 2017)
This review paper covered stress, management related to asthma, trauma, sepsis, inflammation along with anxiety, and depression that occurs both in women with asthma, traumatic children and adult patients. These areas, induce immune function changes, which can lead to both trauma and pro inflammatory activation known as systemic inflammation response syndrome (SIRS). Related to sepsis.Stress management in trauma is based upon the notion that stress causes an immune imbalance in susceptible individuals. Various topics also covered were the neuroimmune system, oxidative stress, inflammation, innate immunity, the role of NF-kappa B related to inflammation, cytokines, procalcitonin related to sepsis.